J = 20
it's very easy, aren't you really able to find that by yourself?
For elimination, multiply one whole equation by negative one (-1), then add or subtract according to your signs. After that, it will be a one-step equation.
3x + 4y = 19 3x + 4y = 19 3x + 4y = 19 -2y = -14 y = 7
3x + 6y = 33 -1 (3x + 6y = 33) -3x - 6y = -33 -14 / -2
Then you would go back and substitute the value of (y) back into either equation and then solve for the remaining variable (x). Finally, use both values to make an ordered pair.
3x + 4y = 19 3x = -9 x = -3 (-3 , 7)
3x + 4(7) = 19 (-9 / 3)
3x + 28 = 19
Good Luck
Answer:
x(x+2)(x-2)(x+1)(x-1)
Step-by-step explanation:
Since both terms are perfect squares, factor using the difference of squares formula,]a^{2} - b^{2} = (a+b)(a-b), where a = x and b = 2.
Add $9.40 two times what ever you get multiply that 15 and there’s your answer